Acute endovascular treatment by coil embolisation of ruptured intracranial aneurysms. - Byrne, J (2001)
Over 5 years, 317 consecutive patients were treated by coil embolisation within 30 days of aneurysm rupture. Neurological deteriorations were recorded in 35 patients during the first 48 h after treatment. In 21 patients these were due to procedural complications, which occurred in 31 procedures (9.8%). The timing of treatment relative to the last subarachnoid haemorrhage (SAH) was compared in patients treated after 0-2, 3-7, 8-14 and 15-30 days. No correlation was found in the incidence of such deteriorations and treatment periods, nor with patient's outcomes at 6 months. However, patients treated within 6 days of SAH had better outcomes than those treated later. Patients should, therefore, be treated as soon as possible after presentation since the technique appears less susceptible to the adverse effects of vasospasm in the 3-10 day period after SAH.